Extent of simultaneous radiation dose and iodine reduction at stable image quality in computed tomography of the chest: A systematic approach using automated tube voltage adaption and iterative reconstructions. Issue 15 (April 2018) - Eller, Achim; Wuest, Wolfgang; Saake, Marc; Ellmann, Stephan; Kaemmerer, Nadine; Hammon, Matthias; Janka, Rolf; Uder, Michael; May, Matthias Stefan
Abstract: Background: Aim of this study was to systematically combine tube voltage adaptation and iterative reconstructions for reduction of iodine and radiation dose. Methods: Settings for the study protocol were evaluated in ex-ante trials to provide image quality that is comparable to a reference protocol at 120 kV with tube current modulation. Consecutive patients were randomized to undergo computed tomography (CT) of the chest using the study protocol (n = 62) or reference protocol (n = 50). Objective and subjective image quality was assessed and compared. Results: Tube voltage was decreased to 100 kV in 47 patients and to 80 kV in 15 patients in the study group. The iodine dosage (16.1 vs 10.5 g) and the effective radiation dose (3.6 vs 2.5 mSv) were significantly decreased in the study group (both P  < .001). Contrast-to-noise ratio was comparable in the pulmonary trunk and increased in the aorta ( P  < .01). Subjective image quality was comparable without statistically significance. Conclusions: Simultaneous reductions in iodine dosage and radiation dose by one-third are feasible for CT of the chest.